Guardians of happiness : Shamanistic tradition in Korean folk painting - Cho, Cha-yong; Emille Misulgwan (Korea); Craft and Folk Art Museum (1973-1997) (Seoul, Korea : Emileh Museum, 1982)
Een mooi geïllustreerd boek waarin we uitvoerig kennis maken met het Koreaanse sjamanisme en mooie voorbeelden krijgen van tekeningen die een weergave zijn van dit geloof.
Catalog of an exhibition held at the Craft & Folk Art Museum in Los Angeles during the USA-Korea Centennial in 1982.